2017
DOI: 10.1002/celc.201600742
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Activity for Glycerol Electro‐Oxidation of Nanostructured Pd−Pt and Pd−Pt−Ru Catalysts

Abstract: Ruthenium-modified palladium/platinum bimetallic materials were synthesized at nanoscale by using the formic acid method. This soft and surfactant-less chemical approach led to a trimetallic catalyst (Pd 25 Pt 25 Ru 50 /C) that displayed excellent ability toward glycerol oxidation and also a favorable capacity for CO oxidation, as a probing molecule. In the case of glycerol, the main oxidation peak shifted remarkably from 500 mV towards lower electrode potentials. From cyclic voltammetry combined with in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Much effort has been spent to synthesize, characterize, and apply new multi‐metallic catalysts for glycerol electrooxidation reaction (GEOR) . Among the emerging catalysts, we should give special attention to Ru‐based materials, since their synthesis has been widely used and improved for almost 30 years . Such knowledge made PtRu nanoparticles (NPs) broadly commercialized and available.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much effort has been spent to synthesize, characterize, and apply new multi‐metallic catalysts for glycerol electrooxidation reaction (GEOR) . Among the emerging catalysts, we should give special attention to Ru‐based materials, since their synthesis has been widely used and improved for almost 30 years . Such knowledge made PtRu nanoparticles (NPs) broadly commercialized and available.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is reasonable to hypothesize that the use of PtRu may improve the electrooxidation of adsorbed CO, which will lead to an enhanced GEOR, accordingly. However, even considering the long‐time‐application of PtRu material in electrocatalysis, few researches have addressed the use of PtRu‐based catalysts for GEOR .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, many endeavors had been paid to push DGFC forward and made great progress by different research groups . Coutanceau et al showed bimetallic Pd 4 Bi porous alloy nanostructures with a mass activity (MA) of around 0.8 A mg −1 Pd toward glycerol electro‐oxidation in KOH electrolyte, and found that aldehydes, ketones, and hydroxypyruvate were the main intermediates .…”
Section: Introductionmentioning
confidence: 99%
“…This approach can also be extended to trimetallic nanoparticles, as shown by Garcia et al . in their recent paper on glycerol oxidation at Pd−Pt−Ru in alkaline media …”
Section: Introductionmentioning
confidence: 99%